Disorders of cardiac hemodynamic in attack period of bronchial asthma in children - Kondratiev V.А.; Reznyk А.V. (Medičnì Perspektivi)
By dopplerechocardiography method there was studied functional state of cardiac ventricles and character of hemodynamic disorders in 48 patients aged 5-17 years in attack period of moderately-severe and severe bronchial asthma. Group of comparison included 40 healthy peers. Disorders of central and peripheral hemodynamic in attack period of bronchial asthma in children were accompanied both by systolic and diastolic dysfunction of the left and right heart ventricles, herewith right ventricle was functioning in the mode of hyperdynamic, and left one – in the mode of hypodynamic. Combined systolic-diastolic variant of dysfunction both of right and left ventricles was developing in 58,3% of patients with moderately-severe and in 91,6% of patients with severe bronchial asthma. In the attack period of bronchial asthma in children equal directionality of systolic and diastolic dysfunction of heart ventricles was developing; this was characterized by synchronization of their function. Assessment of functional interaction of the ventricles under conditions of severe asthma attack showed direct and high (r=0,67) correlative interaction between finding of Tei index of the left and right ventricles, which characterize their systolic function; this, under conditions of increased hemodynamic pre-loading testified to compensatory increase of systolic interaction of ventricles. Direct and high (r=0,69) correlative interaction between time indices of isovolumic relaxation of the left and right ventricles, characterizing their diastolic function, testified to compensatory increase of diastolic interaction of ventricles under conditions of increase of hemodynamic post-loading. Imbalance of central and peripheral link of hemodynamic in attack period of bronchial asthma in children testified to development of cardiac insufficiency, which was compensated predominantly at the expense of increase of heart contractions rate.